2013
DOI: 10.3758/s13415-013-0168-4
|View full text |Cite
|
Sign up to set email alerts
|

I suffer more from your pain when you act like me: Being imitated enhances affective responses to seeing someone else in pain

Abstract: Social-psychological research has suggested that being imitated changes the way that we experience others: We like someone who imitates us more, and the interaction with this person runs more smoothly. Whether being imitated also affects basic social reactions, such as empathy for pain, is an open question. Empathy for pain refers to the observation that perceiving another person in pain results in pain-related brain activation in the observer. The aim of the present study was to combine the two lines of resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 69 publications
2
22
0
Order By: Relevance
“…Other studies have found activation in somato-sensoric areas as well (Morrison et al, 2004;Botvinick et al, 2005;Jackson et al, 2005;Jackson et al, 2006a). Empathy for pain is modulated by pain intensity (Hein and Singer, 2008); contextual factors (Hein and Singer, 2008) such as imitation (De Coster et al, 2013); observer characteristics (Hein and Singer, 2008) such as attention processing and perspective taking ability; alexithymia (Bernhardt and Singer, 2012); prior pain experience (Preis and Kroener-Herwig, 2012;Preis et al, 2013); age (Chen et al, 2014); sex (Coll et al, 2012;Preis and Kroener-Herwig, 2012;Preis et al, 2013); and variables of the observed person (Hein and Singer, 2008) such as affection, similarity to the observer (Preis and Kroener-Herwig, 2012) or group membership (Hein and Singer, 2008;Xu et al, 2009;Hein et al, 2010;Cheon et al, 2011;Bernhardt and Singer, 2012;Montalan et al, 2012).…”
Section: Empathy For Painmentioning
confidence: 99%
“…Other studies have found activation in somato-sensoric areas as well (Morrison et al, 2004;Botvinick et al, 2005;Jackson et al, 2005;Jackson et al, 2006a). Empathy for pain is modulated by pain intensity (Hein and Singer, 2008); contextual factors (Hein and Singer, 2008) such as imitation (De Coster et al, 2013); observer characteristics (Hein and Singer, 2008) such as attention processing and perspective taking ability; alexithymia (Bernhardt and Singer, 2012); prior pain experience (Preis and Kroener-Herwig, 2012;Preis et al, 2013); age (Chen et al, 2014); sex (Coll et al, 2012;Preis and Kroener-Herwig, 2012;Preis et al, 2013); and variables of the observed person (Hein and Singer, 2008) such as affection, similarity to the observer (Preis and Kroener-Herwig, 2012) or group membership (Hein and Singer, 2008;Xu et al, 2009;Hein et al, 2010;Cheon et al, 2011;Bernhardt and Singer, 2012;Montalan et al, 2012).…”
Section: Empathy For Painmentioning
confidence: 99%
“…In this way, the effects of parental reassurance in response to a child's pain may engender quite different results depending on the tone in which the message was communicated [64]. Similarly, efforts to distract a pain sufferer with humour are likely to rely a great deal on what is communicated by the facial expression of the pain observer/caregiver [18,52,71]. A complementary mechanism may be an observer's sensitivity to feedback cues provided by the person in pain [72,73].…”
Section: The Relationship Between Emotion and Motivation In Painmentioning
confidence: 99%
“…), and potential mechanisms of action. unfairness of the pain experience, and prejudicial/discriminatory beliefs or attitudes [3,18,19,20,40,87]. Type of relationship between pain observer and sufferer is likely important here.…”
Section: The Role Of Emotion Regulationmentioning
confidence: 99%
“…We have recently developed a paradigm that allows investigating the effect of modulating self-other distinction on empathic responding when observing someone else in pain (empathy for pain; Singer et al, 2004), by introducing an imitation manipulation (De Coster et al, 2013). In this study, typically developing adults (TD) were either being imitated by a videotaped hand on screen or not prior to observing this hand on screen in pain.…”
Section: Introductionmentioning
confidence: 99%